2016
DOI: 10.1016/j.ijrobp.2015.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Value of Magnetic Resonance Imaging Without or With Applicator in Place for Target Definition in Cervix Cancer Brachytherapy

Abstract: Pre-BT MRI helps to define CTVHR before BT implantation appropriately, if only CT images with the applicator in place are available for BT planning. Significant improvement is achievable in limited-volume stage IIB and IIIB tumors. In more advanced disease (extensive IIB to IVA), improvement of conformity is possible but may be associated with geographic misses. Limited impact on precision of CTVHR-CT is expected in stage IB tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 29 publications
1
31
0
Order By: Relevance
“…These included (i) CT-based CTV: CT with applicator insertion [13, 14], (ii) CT-based CTV HR : CT with applicator insertion and MRI just before first brachytherapy [15], and (iii) MRI-based CTV HR : MRI with applicator insertion [1, 2]. For all CTV contouring modalities, clinical examination findings at the time of brachytherapy were also used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These included (i) CT-based CTV: CT with applicator insertion [13, 14], (ii) CT-based CTV HR : CT with applicator insertion and MRI just before first brachytherapy [15], and (iii) MRI-based CTV HR : MRI with applicator insertion [1, 2]. For all CTV contouring modalities, clinical examination findings at the time of brachytherapy were also used.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the tumor size and topography on MRI just before brachytherapy will be used as the reference in the present recommendations. When complex tumor volumes on MRI without applicator insertion before brachytherapy are visually translated into CT-based CTV HR contouring, there is a potential risk of geographical misses for extensively large tumors with parametrial or adjacent organ involvement [15]. Therefore, greater attentiveness is necessary to minimize such risks in extensively large tumors when determining their sizes and topographies using transverse, coronal and sagittal plane images on MRI.…”
Section: Resultsmentioning
confidence: 99%
“…However, the disadvantage is that patients require more insertional procedures and the reproducibility of inserted applicators needs to be validated. Alternatively, if resources are limited, a standard pre-brachytherapy MRI (without applicators in situ ) can be obtained to evaluate tumor shrinkage and to increase the accuracy of HR-CTV contouring on the CT with applicator in situ [43]. …”
Section: Imaging – Mri/us/ctmentioning
confidence: 99%
“…Alternatively, Potter et al demonstrated a methodology, in which a pre-treatment MRI is performed prior to performing an implant. Their study found that the pre-BT MRI helped define HR-CTV, especially compared to CT images with the applicator in place [53]. Tait et al utilized a similar approach with a pre-implantation MRI, which was fused to the planning CT.…”
Section: Discussionmentioning
confidence: 99%